Implikasi Putusan MK No. 22-24/Puu-VI/2008 Terhadap Model Affirmative Action (Studi di DPRD Provinsi Jawa Tengah Hasil Pemilu Legislatif 2009) - Pusat Kajian Konstitusi FH-Universitas 17 Agustus 1945 Semarang (The Constitutional Court of the Republic of Indonesia, 2016)
After the Constitutional Court decision number 22-24/PUU-VI/2008, there are a shift competition between political parties for candidate-between, especially in political parties. It also implies the strategy of the campaign. Acquisition of candidates for seats in the Parliament of the province of Central Java went from 15 seats in the elections of 2004 to 21 seats in the elections of 2009. This increase was caused by political parties factor, the figure of the candidates, and campaign strategy, as well as a small number of candidates. In nomerik there are 92 between 100 candidates were elected in a small number (1,2,3) and especially among the 21 candidates selected, 20 women also occupy the small number (1,2,3). Recommendation for these problems are: the provisions of the article and / or clause which States that... List of candidates have been prepared on the basis of the number of series that contains at least 30% (thirty percent) of the representation of women is maintained and is complemented by the formula in each electoral district; The provisions of article and/or the point of, which states that ... In the list of candidates will be every three (3) candidates, at least one (1) of female candidates was retained and supplemented formula ... In the list of candidates will be every three (3) candidates, at least 1 (one) female candidate who was placed on a small number of not less than 30% (thirty percent) of the number of constituencies, and the future of affirmative action based models quota of 30 % (thirty percent) and zipper for women candidates and the placement model in a limited number is not sufficient to maintain a procedure, but must be accompanied by the development of the cultural climate of recruitment politician in their respective political parties competing in elections and the increase in the specific political education for women.